Analisis Semantik Secara Meluas Pada Media Sosial “Facebook” - Nurhayati; Katharina Woli Namang (Hikamatzu | Journal of Multidisciplinary, 2024)
Language is a sound symbol used by members of a society to interact, cooperate and identify themselves. Therefore, language produces new words and new meanings which aim to meet communication needs. The problem discussed is the widespread change in meaning found in statuses and comments on Facebook media and what factors cause the word to undergo widespread change. Then the word is compared with the previous meaning or actual meaning. Based on the results of the discussion, 30 (thirty) forms of widespread changes in meaning were found.